New Bedford's Civil War - Mulderink, Earl F. (North's Civil War., 2012)
This book examines the social, political, economic, and military history of New Bedford, Massachusetts, in the nineteenth century, with a focus on the Civil War homefront from 1861 to 1865 and on the city's black community, soldiers, and veterans.